2017
DOI: 10.1080/00380768.2017.1322918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the long-term application of anaerobically digested residual slurry on methane emissions in a rice paddy field

Abstract: The anaerobic digestion of livestock manure is an environmentally compatible technology used for the production of renewable energy. Anaerobically digested residual slurry has been used worldwide as a liquid fertilizer in both upland and paddy fields. However, a controversial question remains as to whether the application of slurry to rice paddy fields increases methane emissions; although methane is one of the most prevalent greenhouse gases, little is known about the effects of the long-term application of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Although the inputs of P and K from effluent were different from those in U3.25, these comparisons suggest that urea was more effective N-fertilizer form in this study. This result is consistent with those of Nishikawa et al (2012) and Tanaka et al (2017), so the calculation of N applied from the biogas effluent that we used should be based on NH 4 -N instead of total N. Our study did not reveal significant differences in grain yield among the five E-LCC treatments (Table 3), mainly on account of the high spatial variation, as discussed above. However, the positive linear relationship between grain yield and LCC value (or SPAD value; Figure 3) suggests that a higher LCC threshold than we used would have been favorable in terms of grain production under the current microcosm conditions.…”
Section: Rice Response To Biogas Effluent Applicationsupporting
confidence: 89%
“…Although the inputs of P and K from effluent were different from those in U3.25, these comparisons suggest that urea was more effective N-fertilizer form in this study. This result is consistent with those of Nishikawa et al (2012) and Tanaka et al (2017), so the calculation of N applied from the biogas effluent that we used should be based on NH 4 -N instead of total N. Our study did not reveal significant differences in grain yield among the five E-LCC treatments (Table 3), mainly on account of the high spatial variation, as discussed above. However, the positive linear relationship between grain yield and LCC value (or SPAD value; Figure 3) suggests that a higher LCC threshold than we used would have been favorable in terms of grain production under the current microcosm conditions.…”
Section: Rice Response To Biogas Effluent Applicationsupporting
confidence: 89%
“…This study found that the total CH 4 emission varied from 21.3 to 30.6 g CH 4 m −2 , which was in line with previous reports using cascade effluent for rice fields [17,[19][20][21]24] (Table 4) as well as referring to the VMD's rice fields [34,[54][55][56]. However, the CH 4 emission varied between study sites and livestock's BDE.…”
Section: Effects Of Methanotroph-inoculated Bde On Methane and Nitrou...supporting
confidence: 90%
“…Moreover, reusing BDE for rice paddy fields can improve soil fertility by enriching organic matter, amino acids, bioactive substances, and various nutrients [9,14,15]. In fact, the cascade utilization of digestate for rice cultivation has recently been noticed in terms of its nutrient availability and yield-unsacrificed feasibility [16][17][18]. However, a major concern in employing BDE for rice crops has been remarked as potential risks of higher CH 4 flux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation